2007
DOI: 10.1017/s0033822200042776
|View full text |Cite
|
Sign up to set email alerts
|

Tropical South China Sea Surface 14C Record in an Annually-Banded Coral

Abstract: A surface-water A 14 C record of AD 1948-1999 in the tropical South China Sea (SCS) has been reconstructed from accelerator mass spectrometric radiocarbon measurements of annual bands of a Pontes coral collected from Con Dao Island, Vietnam. Results gave the following A 14 C time series: a steady state of -47.8 ± 2.8%o (mean ± SD, η -8) during 1948-1955 (i.e. in the pre-bomb period); a sharp increase during 1956-1966; a gradual increase during 1967-1973; a relatively high maximum value of ~174%c in 1973; and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 29 publications
(17 reference statements)
0
39
0
Order By: Relevance
“…3a). The average Δ 14 C value in the 1970s was 146.7 ‰, which lies between the average Δ 14 C values in Guam (Andrews et al 2016) and Ishigaki (Hirabayashi et al 2017a) and is lower than that in Con Dao (Mitsuguchi et al 2007) (Fig. 2).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…3a). The average Δ 14 C value in the 1970s was 146.7 ‰, which lies between the average Δ 14 C values in Guam (Andrews et al 2016) and Ishigaki (Hirabayashi et al 2017a) and is lower than that in Con Dao (Mitsuguchi et al 2007) (Fig. 2).…”
Section: Resultsmentioning
confidence: 70%
“…Con Dao Island lies on the Sunda Shelf in the southwestern SCS, where the waters are very shallow (Mitsuguchi et al 2007). Mitsuguchi et al (2007) suggested that the ∆ 14 C record in Con Dao is primarily related to monsoon-induced air-sea gas exchange in the semienclosed shallow waters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dang et al (2004) and Mitsuguchi et al (2007Mitsuguchi et al ( , 2008 have attributed this early rise and the enriched values to the shallow location of the coral on the Sunda shelf. Indeed, its location is isolated as it lies 300 km from the deeper SCS basin.…”
Section: Post-bomb Period 1954 To 1986mentioning
confidence: 99%